All-inside versus inside-out suture techniques in arthroscopic meniscus repair: A prospective randomized study protocol. Issue 27 (2nd July 2020) - Lin, Yanming; Zhao, Jiasong; Qiu, Heng; Huang, Yong
Abstract: Background: With advancements in our understanding of meniscal function, treatment options for meniscal injuries have evolved considerably over the past few decades. The aim of the current study was to compare the all-inside and inside-out techniques with regard to retear rate, functional outcomes, and perioperative complications in patients who had undergone arthroscopic meniscus repair. We hypothesized that there was no significant difference between the 2 groups in terms of postoperative outcomes after arthroscopic meniscus repair. Methods: This study was a prospective randomized blinded study, with a parallel design and an allocation ratio of 1:1 for the treatment groups. This study was approved by the Institutional Review Board in our hospital and written informed consent was obtained from all subjects participating in the trial. It was carried out in accordance with the principles of the Helsinki Declaration. A total of 70 patients who meet inclusion criteria are randomized to either all-inside or inside-out group. The primary outcome measure was retear rate. Retear was determined by repeat arthroscopic evaluation of patients with follow-up for symptoms of persistent or new pain, catching, or locking that was possibly related to the meniscal repair. Secondary outcomes included disease-specific quality of life measurement with the Western Ontario Meniscal Evaluation Tool, range of motion, operative time, and adverse events at surgery or throughout the follow-up period. Results: This study has limited inclusion and exclusion criteria and a well-controlled intervention. Trial registration: This study protocol was registered in Research Registry (researchregistry5589).